Evaluasi Sistem Manajemen Informasi Objek Pajak dalam Pemungutan PBB-P2 di Badan Pendapatan Daerah Kota Bekasi - Su'fatul Ulum Mutatun Afia; Cecep Wahyu Hoerudin (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2020)
The Tax Object Information Management System (SISMIOP) is a management information system application that is used to help collect PBB-P2. In its implementation, it needs to be evaluated to assess how its performance. The purpose of this study is to find out how the Evaluation of the Tax Object Information Management System (SISMIOP) in Land and Building Tax Collection in Rural and Urban Cities (PBB-P2) in Bekasi City Bapenda and SISMIOP advantages and disadvantages in the PBB-P2 Collection in Bekasi City Bapenda. The research method used is a qualitative method with a descriptive approach, using interviews, observation, documentation studies, and triangulation as data collection techniques. The result of this research is the evaluation of SISMIOP in PBB-P2 Collection in Bekasi City Bapenda has a good assessment. The SISMIOP application has fulfilled all three aspects of eligibility. However, in the implementation of tax collection, the imposition of PBB-P2 tax has not been evenly distributed to the whole community because there are still unregistered tax objects and the lack of field verification team employees so that it cannot record the full potential of the Bekasi City PBB-P2.